PENILAIAN HASIL PEMBELAJARAN KEMAHIRAN BERBAHASA INDONESIA DENGAN PENDEKATAN KOMUNIKATIF - Sumadi Sumadi (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstract: Assessment of the Indonesian Language Learning Outcomes Using theCommunicative Approach. Since the 1994 Curriculum was launched up to now,the assessment of the Indonesian language learning outcomes has been directed tothe students ability to use Indonesian communicatively in real situations.However, many teachers still assess such an ability based on the studentstheoretical knowledge, not on their communicative ability. This might happenbecause of the teachers lack of understanding about the use of the communicativeapproach in the Indonesian language learning. This article discusses the assessmentof the Indonesian language learning outcomes using the communicative approach.The discussion consists of the assessment philosophy, techniques and procedures,rubrics, and sample test items constructed based on the communicative approach.Keywords: assessment, communicative approach